Mathematical modeling and stability of SARS-CoV-2 transmission dynamics among domestic tourists in Thailand - Sungchasit, Rattiya; Pongsumpun, Puntani (My University, 2025)
The defined epidemiological model system explaining the spread of infectious diseases characterized with SARS-CoV-2 is analysed. The resulting SEIQR model is analysed in a closed system. It considers the basic reproductive value, the equilibrium point, local subclinical stability of the disease-free equilibrium point and local subclinical stability of the endemic equilibrium point. This is examined and the asymptotic dynamics of the appropriate model system are investigated. Further, a sensitivity analysis supplemented by simulations is prepared in advance to impose how changes in parameters involve the dynamic behaviours of the model.
Keywords: Asymptotic dynamics; Basic reproductive number; Mathematical model; Numerical simulations; Stability